2021
DOI: 10.1017/s0016756821000522
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic exhumation of the Jueluotage area, Eastern Tianshan, NW China: constraints from (U–Th)/He and fission-track thermochronology

Abstract: The Jueluotage area, which is located in the southern branch of the Eastern Tianshan and northeast of the Tarim Basin, represents a vital locality for investigating intracontinental reactivation induced by the tectonic events at the Eurasian plate margin. This study applies zircon and apatite (U–Th)/He and apatite fission-track thermochronology to the Jueluotage area in the Eastern Tianshan. Our data and thermal history modelling show that the Jueluotage area experienced Triassic–Early Jurassic (˜240–180 Ma) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
(137 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the distinguished age populations (peaks) are in good agreement with the basement cooling ages (both AFT and apatite (U-Th)/He) reported from the Harlik, Kangguer, and Yamansu Arcs in the eastern Chinese Tianshan (e.g. Gillespie et al 2017a;Sun et al 2021;He et al 2022a). The denudation of these basement rocks hence has provided a large volume of sediments to the adjoining and long-lived basins.…”
Section: Thermochronological Datasupporting
confidence: 80%
“…Furthermore, the distinguished age populations (peaks) are in good agreement with the basement cooling ages (both AFT and apatite (U-Th)/He) reported from the Harlik, Kangguer, and Yamansu Arcs in the eastern Chinese Tianshan (e.g. Gillespie et al 2017a;Sun et al 2021;He et al 2022a). The denudation of these basement rocks hence has provided a large volume of sediments to the adjoining and long-lived basins.…”
Section: Thermochronological Datasupporting
confidence: 80%
“…In recent years, research on the Mesozoic sedimentary system in Tianshan (Hendrix et al, 1992;Han et al, 2016a;De Pelsmaeker et al, 2018) and detrital zircon U-Pb geochronology in Bogda region and Turpan-Hami Basin (Tan et al, 2014;Wang J et al, 2018;Zhang et al, 2019) indicated a significant surface uplift and exhumation phase of the Tianshan range during the Triassic. In addition, the study of strike-slip deformation in eastern Tianshan (Wang et al, 2010) and tectonothermal events in the Tianshan range (Li and Wang, 1998;Li et al, 2000;Dumitru et al, 2001;Seltmann et al, 2011;Zhao et al, 2020;Sun et al, 2021;He et al, 2022) also indicated obvious Triassic tectonic reactivation in the Tianshan range. However, there is no report about the initial timing and deformation process of the Triassic intracontinental deformation in the Tianshan range, which are crucial to clarify the early construction of the Asia continent in the early Mesozoic.…”
Section: Introductionmentioning
confidence: 99%